Adoption disclosure: experiences of Indian domestic adoptive parents. (11th September 2014) - Mohanty, Jayashree; Ahn, Jaejin; Chokkanathan, Srinivasan
Abstract: Adoption disclosure is an important indicator of the healthy development and psychological well‐being of adopted children. However, findings from studies conducted among Asian domestic adoptive parents have highlighted some concerns. Using Kirk's theoretical proposition, a study was conducted among 86 Indian domestic adoptive parents to determine the societal and familial factors related to adoption disclosure. The results showed that while many of the parents had talked openly about their adoption to their immediate families (95.3%) and others of their social network (88.4%), they were hesitant in telling the child. Only 12.8% of the Indian parents had told their child about adoption, and 31.4% were planning to tell. The results of the logistic regression analysis revealed that children who were above 6 months at adoption were more likely to have had disclosures from their parents about their adoption. Further, adoptive parents who had told or were planning to tell their child about adoption perceived less about the loss of the biological parenthood and were more likely to perceive the beneficial effects of adoption disclosure to the child. These findings have implications for the provision of appropriate strategies, resources and support to adoptive families seeking to deal with adoption disclosure.